Experiences of augmented arm rehabilitation including supported self-management after stroke: a qualitative investigation. (February 2021) - Schnabel, Stefanie; van Wijck, Frederike; Bain, Brenda; Barber, Mark; Dall, Philippa; Fleming, Alexander; Kerr, Andrew; Langhorne, Peter; McConnachie, Alex; Molloy, Kathleen; Stanley, Bethany; Young, Heather Jane; et al.
Objective: To explore the experiences of stroke survivors and their carers of augmented arm rehabilitation including supported self-management in terms of its acceptability, appropriateness and relevance. Design: A qualitative design, nested within a larger, multi-centre randomized controlled feasibility trial that compared augmented arm rehabilitation starting at three or nine weeks after stroke, with usual care. Semi-structured interviews were conducted with participants in both augmented arm rehabilitation groups. Normalization Process Theory was used to inform the topic guide and map the findings. Framework analysis was applied. Setting: Interviews were conducted in stroke survivors' homes, at Glasgow Caledonian University and in hospital. Participants: 17 stroke survivors and five carers were interviewed after completion of augmented arm rehabilitation. Intervention: Evidence-based augmented arm rehabilitation (27 additional hours over six weeks), including therapist-led sessions and supported self-management. Results: Three main themes were identified: (1) acceptability of the intervention (2) supported self-management and (3) coping with the intervention. All stroke survivors coped well with the intensity of the augmented arm rehabilitation programme. The majority of stroke survivors engaged in supported self-management and implemented activities into their daily routine. However, the findings suggest that some stroke survivors (male >70 years) had difficulties with self-management, needing a higher level of support. Conclusion: Augmented arm rehabilitation commencing within nine weeks post stroke was reported to be well tolerated. The findings suggested that supported self-management seemed acceptable and appropriate to those who saw the relevance of the rehabilitation activities for their daily lives, and embedded them into their daily routines.